Genetic Manipulation of Francisella Tularensis - Zogaj, Xhavit; Klose, Karl E. (Frontiers in Microbiology, 2011)
Francisella tularensis is a facultative intracellular pathogen that causes the disease tularemia. F. tularensis subsp. tularensis causes the most severe disease in humans and has been classified as a select A agent and potential bioweapon. There is currently no vaccine approved for human use, making genetic manipulation of this organism critical to unraveling the genetic basis of pathogenesis and developing countermeasures against tularemia. The development of genetic techniques applicable to F. tularensis have lagged behind those routinely used for other bacteria, primarily due to lack of research and the restricted nature of the biocontainment required for studying this pathogen. However, in recent years, genetic techniques, such as transposon mutagenesis and targeted gene disruption, have been developed, that have had a dramatic impact on our understanding of the genetic basis of F. tularensis virulence. In this review, we describe some of the methods developed for genetic manipulation of F. tularensis.